Geotechnical monitoring during construction in difficult soil conditions - Bredikhin Vladimir (Institut za istrazivanja i projektovanja u privredi, 2021)
One of the common and at the same time most difficult problems that developers may face is unstable soil layer at the base of a future building. This paper describes problems of construction on weak, subsidence and heaving soils in engineering and geological conditions of Kursk city. Real problem of construction property safety is shown with the example of one of the demanding geomorphological and lithological conditions of urban areas. The paper offers a description of geologic and hydrogeological features of the slope rock mass in the right bank of the Tuskar river. Groundwater level lies at 8.7 m. depth. It is possible to predict an increase in the level of groundwater in building maintenance because this area is potentially flooded. Various engineering and geological processes and such phenomena as ground subsidence, Karst, suffosia, landslides, flooding, etc., can also be found in the studied territory. Initially an insufficient engineering-geomorphological, hydrogeological, ecological and engineering-geological study of hazardous areas in the city of Kursk have led to its problematic development, which illustrates the situation with residential real estate in the studied territory. To predict dangerous engineering-geological processes and ensure the reliability of the construction fund, specific proposals have been developed for the organization of a geotechnical monitoring system based on the optimal integration of geomorphological, geodesic, engineering-geological, hydrogeological and environmental construction methods in complex engineering-geological conditions.